IncluCity: using contextual cues to raise awareness on environmental accessibility - Goncalves, Jorge; Kostakos, Vassilis; Hosio, Simo; Karapanos, Evangelos; Lyra, Olga (My University, 2013)
Awareness campaigns aiming to highlight the accessibility challenges affecting people with disabilities face an important challenge. They often describe the environmental features that pose accessibility barriers out of context, and as a result public cannot relate to the problems at hand. In this paper we demonstrate that contextual cues can enhance people's perception and understanding of accessibility. We describe a two-week study where our participants submitted reports of inaccessible spots all over the city through a web application. Using a 2×2 factorial design we contrast the impact of two types of contextual cues, visual cues (i.e., displaying a picture of the inaccessible spot) and location cues (i.e., ability to zoom-in the exact location). We measure participants' perceptions of accessibility and how they are challenged to consider their own limitations and barriers that may also affect themselves in certain circumstances. Our results suggest that visual cues led to a bigger sense of urgency while also improving participants' attitude towards disability.
Keywords: Accessibility; Civic engagement; Contextual cues; Disability; Inclusion